2006
DOI: 10.3892/or.15.4.861
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of protein-bound polysaccharide K plus tegafur/uracil in patients with stage II or III colorectal cancer: Analysis of immunological parameters

Abstract: Protein-bound polysaccharide K (PSK) increased the 5-year disease-free survival rate and reduced the risk of recurrence in a randomised, controlled study for stage II and III colorectal cancer. In order to elucidate the disease-free survival benefits with PSK and what immunological markers could indicate a PSK responder, serial changes in immunological parameters were monitored in the study. PSK decreased the mean serum immunosuppressive acidic protein (IAP) level, and increased the mean population of natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…However, it could restore a depressed immunological responsiveness as seen in cancer or with chemotherapy (Chu et al, 2002). Various experimental evidences showed that the antitumor action of CV polysaccharides is due to the enhancement and potentiation of cell-mediated immune system through the regulation of immunomodulatory cytokines and activation of the complement system and Natural Killer Cells (Ohwada et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, it could restore a depressed immunological responsiveness as seen in cancer or with chemotherapy (Chu et al, 2002). Various experimental evidences showed that the antitumor action of CV polysaccharides is due to the enhancement and potentiation of cell-mediated immune system through the regulation of immunomodulatory cytokines and activation of the complement system and Natural Killer Cells (Ohwada et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PSK has been shown to regulate cytokines and activate the complement system and natural killer cells. 31 It has also been reported that PSP effectively stimulates the generation of IFN-α and markedly improves the production of IFN-γ. 32 The latter is of special interest to us as our laboratory has previously reported that peripheral blood dendritic cells from myeloma patients were defective in their ability to up-regulate the expression of CD80 when ligating with CD40-ligand partly due to the presence of cytokines of IL-10 and TGF-β.…”
Section: The Use Of Coriolus Versicolor In Cancer Managementmentioning
confidence: 97%
“…It has been reported to be of potential benefit as adjuvant mono-or combination treatment in e.g. colorectal [10][11][12], breast [13][14], liver [15], pancreatic [16][17][18], gastric [19][20][21][22], esophageal [23], and lung cancer [24][25][26][27]. Furthermore, PSK has demonstrated minimal cytotoxicity or other side effects commonly associated with conventional anticancer treatments [28].…”
Section: Actions Of Psk In Cancermentioning
confidence: 99%